Clinician's Guide to the Diagnosis and Management of Tooth Sensitivity - Taha, Sahar.; Taha, Sahar.; Clarkson, Brian H.; Clarkson, Brian H. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Tooth sensitivity, or dentin hypersensitivity, has a high prevalence among the general population and is a very common cause of visits to the dentist. This concise, easy-to-read guide provides the clinician with the most important information required for the correct diagnosis and effective management of dentin hypersensitivity. After discussion of theories regarding the underlying mechanisms, predisposing medical and dental conditions are reviewed. The route to an accurate diagnosis, based on determination of the precise cause, is then explained. A range of potential treatment approaches and their applications are discussed, including dentin blocking agents, nerve desensitization, restorative approaches, and periodontal surgery. Preventive, at-home, and in-office treatment modalities are all described, and future treatments are also considered. Helpful flowcharts are included that will facilitate decision making.